Image resolution enhancement using improved edge directed interpolation algorithm / Md Shamim Hossain - Md Shamim , Hossain (2018)
Image resolution enhancement is a process to convert the low-resolution image into high-resolution image. This method is applied in many image processing field. One of the commonly used techniques for image resolution enhancement is interpolation. The results of pixel interpolation can vary significantly depending on the interpolation algorithm. Moreover, the conventional interpolation methods are not efficient to assign accurate interpolation value to the high-resolution edge pixels. Therefore, in this study, we propose an improved edge directed interpolation algorithm, which is able to preserve the sharpness of edges. The proposed method is divided into three main steps: edge pixel filtering; bi-cubic interpolation, and edge directed interpolation. The edge pixels and non-edge pixels are separated by the adaptive edge filtering method. After that bi-cubic interpolation is applied for non-edge pixels. The Lagrange interpolation polynomial is used for bi-cubic interpolation and the average weight of sixteen neighbour pixels are calculated for each high-resolution non-edge pixel. Finally, an improved edge directed interpolation is applied on the edge pixels. The proposed method is tested on the several standard grayscale images and compared with the existing methods. According to the evaluation results, the proposed method provides the highest performance of the subjective and objective quality than the standing edge directed interpolation methods.